1990
DOI: 10.1177/001872679004301103
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity and the Handicapping Functions of Stereotypes: Children's Understanding of Mental and Physical Handicap

Abstract: Data from a pilot study established that, in reference to people with mental handicap and physical disabilities, I1-year-old subjects tended only to use the terms "mentally handicapped," "physically handicapped," and the colloquial term "divvy." The main study asked children to rate a target child ascribed one of these labels (or the label "normal"), and to complete a measure of social distance from that target. In addition, subjects were divided into those with high or low prior contact with people with menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Other studies have also shown that younger children lack knowledge about learning or physical difficulties (Lewis, 1993;Lewis & Lewis, 1987;Nabors & Keyes, 1995). Older children seem to be better informed (Magiati et al, 2002), although Abrams et al (1990) found that 10-year-old children grouped different disabilities into one general category. In the current study, themes associated with children's ideas about the causes of learning and physical difficulties were mutually exclusive, suggesting that younger and older children can distinguish between them.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have also shown that younger children lack knowledge about learning or physical difficulties (Lewis, 1993;Lewis & Lewis, 1987;Nabors & Keyes, 1995). Older children seem to be better informed (Magiati et al, 2002), although Abrams et al (1990) found that 10-year-old children grouped different disabilities into one general category. In the current study, themes associated with children's ideas about the causes of learning and physical difficulties were mutually exclusive, suggesting that younger and older children can distinguish between them.…”
Section: Discussionmentioning
confidence: 95%
“…Lewis suggested that young children may be influenced by their parents' lack of knowledge or negative stereotypes, and may be more aware of physical differences than intellectual differences. However, Abrams et al (1990) found that older children had difficulties distinguishing between different types of disabilities. They asked 10-year-old children to select correct definitions for the terms "mental handicap", "physical handicap", and "normal".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with intellectual disabilities are at risk for social isolation, neglect or rejection by their classmates (Nowicki 2003; Norwich & Kelly 2004; Ring & Travers 2005). Discrimination against individuals with intellectual disabilities is a consistent finding, which is not surprising given that attitudes are frequently negative (Abrams et al. 1990; Nabors & Keyes 1995; Cohen & Lopatto 1995; Harper 1997; Okagaki et al.…”
Section: Introductionmentioning
confidence: 80%
“…Cole, 1999;Loxley and Thomas, 1997;Knight, 1999) and research evaluating the effects of inclusion is limited (Tilstone and Rose, 2000;Tod, 1999). Nevertheless there is some evidence that people with learning dif®culties experience serious problems within the mainstream educational system and often end up as adults living`on the fringes of society' (Abrams et al, 1990;Szivos-Bach, 1993;Szivos and Grif®ths, 1990). This may result from that fact that interactions with peers without learning dif®culties are adversely affected by poor self-worth, resulting from adverse comparison with a non-stigmatized group (Szivos-Bach, 1993).…”
Section: Discussionmentioning
confidence: 99%